The effects of problem based learning on knowledge acquisition, critical thinking, and intrinsic motivation of electrical engineering students - Masek, Alias (2012)
It is timely with the agenda of polytechnic educational transformation, this research was initiated to examine the effects of Problem Based Learning (PBL) on students’ knowledge acquisitions, critical thinking ability, and intrinsic motivation and thus to propose a PBL instructional procedure, for the polytechnic’s electrical engineering course. An experiment, consisting of pre-test and post-test, was carried out on 53 undergraduate students of electrical engineering course, who attended the Electrical Technology Module (ET101) in their first semester. A control group was maintained in order to verify the results of the experiment. The treatment used a special design of PBL procedures in the experimental group for a ten weeks period, and the existing method of conventional teaching was retained in the control group. Participants completed pre-test and post-tests based on three instruments: knowledge acquisition test, translated version of The Cornell Critical Thinking Test Specimen set, and intrinsic motivation questionnaire. The data were analysed using MANCOVA and results were obtained. Students’ knowledge acquisition in the PBL group was significantly higher than that of their counterparts [F (1, 44) = 5.37, p < 0.05], with medium effect size (d = .68). Students’ intrinsic motivation in the PBL group was significantly higher than that of their counterparts, [F (1, 44) = 5.18, p < 0.05], with medium effect size (d = .68). However, students’ critical thinking ability in the PBL group was not significantly different from that of their counterparts in the TLA group [F (1, 44) = .019, p > 0.05]. Therefore, it can be concluded that PBL enhances students’ knowledge acquisitions and intrinsic motivation, but does not improve students’ critical thinking ability as compared to conventional approach. The implication is that the PBL procedures used in this study may be useful for educators in polytechnics, though some modifications are required to fine-tune the original framework for future implementation.